Teachers’ experiences using networked technologies for teaching - Cutajar, Maria (Proceedings of the International Conference on Networked Learning, 2018)
At a given Maltese Higher Education complex there is increasing drive to encourage teaching academics to incorporate networked technologies in their teaching therefore expanding face-to-face campus-based education to blended and online provision. This paper reports on research findings of an explorative study investigating variation in academics’ accounts of their experiences using networked technologies for teaching in this local context. Twenty-seven participating academics were purposively chosen from different faculties, institutes, centres and colleges. The sample was also balanced in terms of tenure, ranking, gender and age. Phenomenographic analysis of interview transcript data led to a configuration made up of 5 hierarchically inclusive categories describing the act of using networked technologies for teaching as: (i) Accumulating subject content for passing on to students for learning; (ii) Motivating and accommodating students to understand subject content in learning; (iii) Building a positive teacher-student rapport in extending students’ learning; (iv) Modelling behaviour inspiring students to exploratory learning; (v) Fostering a community of learners participating and convening in dialogic learning. These categories of description are also configured as structurally threaded by three critical themes of expanding awareness including perceived affordances of networked technologies for teaching, human roles in teaching, and teaching pedagogic strategy. This phenomenographic description suggests a watershed between the third and fourth categories going from the incorporation of networked technologies in teaching activity for their auxiliary capacity for learning - teaching as transmission (of subject knowledge, of understanding, of empathy), to the incorporation of networked technologies as a seamless facet of teaching activity - teaching as participation (in exploratory learning, in dialogic learning). This description of variation in teachers’ accounts of their experiencing using networked technologies for teaching confirms previous research but also adds new detail and insight. Besides, the resultant configuration projected as an emergent progression of expanding awareness is reckoned a means for positively inspiring network enhanced development of teaching practices. The thinking about variation in teachers’ experiences as promoted by this research is potentially a means to encourage and facilitate the professional development of teaching academics steering away from pressure for change. Potentially it evokes a constructive outward view in the attempt to support best practices in HE teaching.